UPAYA MEREDUKSI DAGING SAPI GLONGGONGAN MELALUI PELATIHAN PEMBUATAN SUPLEMEN PAKAN TERNAK RUMINANSIA MENGGUNAKAN UMMB (UREA MOLASES MULTINUTRIENT BLOK) DENGAN METODE PERUNUT RADIOISOTOP - Pujianto, Sugi Rahayu, Dyah Purwaningsih, (Universitas Negeri Yogyakarta, 2011)
This Community Service Program (PPM) is triggered by the rise ofbeef traders who sell glonggongan (i.e, pale, soft, and exudates (PSE)) beefas an unfair profit-seeking at the expense of consumer by providingunhealthy, mistreated glonggongan meat. To reduce such a practice, itnecessary to find a healthy way of profitably fattening the cattle. Thesupplementation of cattle feed is one alternative. This Community Serviceactivity aims to: (1) assess the prospects for the use of UMMB supplementsin Jatisarono, Nanggulan District, Kulon Progo Regency in relations to theaspects of community development in a longer term, (2) advise the publicabout the use of UMMB supplements based on the use of radioisotope tracerfor the interests of community of farmers, and (3) provide information to thepublic about the socio-cultural aspects of the use of UMMB supplements insearch for new entrepreneurships.The target audience of the Program is the cow farmer in Jatisaronovillage, District of Nanggulan, Kulon Progo Regency, amounting to 27people. The Methods of Activities include lectures, discussions, information,workshops, limited dissemination. The stages of activity are set asfollows: (1) explaining to the trainees about the various ways for increasedproductivity of beef, (2) discussing the negative impact of unhealthyglonggongan cattle production in terms of health and business, (3) exploringways to overcome difficulties in maintaining beef cattle that can producehigh quality beef, and (4) inviting the participants to practice the productionof UMMB fodder supplements.Upon completion of this program, it is noticed that the cow farmer inJatisarono village became knowledgeable of: (1) the importance of UMMBfodder supplement, (2) the negative effects of unhealthy practice offattening cattle (glonggongan) in terms of health and business, (3) themanure and various elements contained in it to find indicators of the healthlevel of their cattle, (4) the mechanism of production and application ofUMMB fodder supplementAs a follow up, it is expected that cow farmers in Jatisarono village,District of Nanggulan, Kulon Progo will start establishing group to producethe fodder supplement. It is intended for pioneering entrepreneurship andreducing the socio-cultural problems posed by the circulation of unhealthy(glonggongan) beef.